Minimum area, low cost fpga implementation of aes - Liberatori, Mónica Cristina (2004)
The Rijndael cipher, designed by Joan Daemen and Vincent Rijmen and recently selected as the official Advanced Encryption Standard (AES) is well suited for hardware use. This implementation can be carried out through several trade-offs between area and speed. This paper presents an 8-bit FPGA implementation of the 128-bit block and 128 bit-key AES cipher. Selected FPGA Family is Altera Flex 10K. The cipher operates at 25 MHz and consumes 470 clock cycles for algorithm encryption, resulting in a throughput of 6.8 Mbps. The design target was optimisation of area and cost.